Prevalencia de fracturas de radio y cúbito del Hospital Julius Doepfner de la ciudad de Zamora. - Castro Vásquez, José Omar (2018)
A fracture can be defined as the interruption of bone or cartilage continuity. The radius or ulna may fracture separately or both. In this way, I decided to carry out this research process, setting the general objective: To determine the prevalence of radio and cube fractures at the Julius Doepfner Hospital in the city of Zamora. And as specific objectives: Establish the number of radio and cube fractures according to age, gender and occupation. Identify the mechanism of injury. Establish exposed and unexposed fractures. Determine the applied management. Using a retrospective, quantitative cross-sectional study, whose universe and sample is 40 in 2016 and 33 in 2017. A data collection form was made by the author that allowed me to obtain the following results: the prevalence in the 2016 for every 100 people is (0.13%) of suffering radio and cubicle fractures and 2017 (0.10%), is frequent in males with 63% (n = 46) with occupation of housewives with 30% (n = 22). Followed by farmers with 25% (n = 18), falls from their own height causes radio and cube fractures with 64% (n = 47), direct hits is found with a percentage of 19% (n = 14). The unexposed forearm fractures present a higher percentage with 88% (n = 64), the exposed fractures present 12% (n = 9), the management performed is closed reduction and percutaneous fixation with Kirschner's nail with 48% (n = 35). Followed by closed reduction and immobilization with plaster with 21% (n = 15) Key words: Radius and ulna fractures, Fracture classification, Fracture management.